The challenges of integrated river basin management in India: issues in transferring successful river basin management models to the developing world - International Water Management Institute (International Water Management Institute, 2002)
The problems that river basin institutions in the developed world successfully address?such as pollution, sediment buildup in rivers and the degradation of wetlands?are not the top priorities for Indian policy makers and people. The items that do top Indian agendas?providing access to water for drinking and growing food, eradicating poverty, and stopping groundwater overexploitation?are either unresolved in the developed world or have become irrelevant due to economic development. This does not mean that India and other developing countries cannot learn valuable lessons from models for Integrated River Basin Management. Loosely structured River Basin Organizations, such as Southeast Asia?s Mekong Commission, can contribute to basin welfare by serving as a coordinating mechanism. They can facilitate dialogue and negotiation on resource allocation among organized stakeholders and representative bodies (such as national or state governments sharing a river basin). But River Basin Organizations by themselves cannot be expected to address the more fundamental issues that water sectors in India must contend with.